Pendekatan Dakwah Etis terhadap Kondisi Masyarakat Muslim Heterogen - Hajir Tajiri (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2008)
Da’wah has two faces the existence of which  depends to da’i. When da’wah is done by da’i having minimum competency in knowledge and faith, the performance of da’wah become fearing, in-productive, horrify and fearsome. On the contrary if da’wah is done by da’i having  a lot of knowledge, strong faith, competency in using relevant method, so da’wah’s performance  become good and  applicable to heterogeneous societies.